2019
DOI: 10.1002/ange.201810919
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Affinity Fluorescent Sensor for Catecholamine: Application to Monitoring Norepinephrine Exocytosis

Abstract: A fluorescent sensor for catecholamines, NS510, is presented. The sensor is based on a quinolone fluorophore incorporating a boronic acid recognition element that gives it high affinity for catecholamines and a turn‐on response to norepinephrine. The sensor results in punctate staining of norepinephrine‐enriched chromaffin cells visualized using confocal microscopy indicating that it stains the norepinephrine in secretory vesicles. Amperometry in conjunction with total internal reflection fluorescence (TIRF) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Surely, after the probe was cultured with PC12 cells in similar conditions, an obvious red fluorescence emission could be observed and it increased over time (Figure ). The results showed that the probe could mark the norepinephrine in the vesicle …”
Section: Resultsmentioning
confidence: 93%
“…Surely, after the probe was cultured with PC12 cells in similar conditions, an obvious red fluorescence emission could be observed and it increased over time (Figure ). The results showed that the probe could mark the norepinephrine in the vesicle …”
Section: Resultsmentioning
confidence: 93%
“…Therefore, we used confocal laser microscopy to monitor the exocytosis of norepinephrine in cells stimulated by a high concentration of potassium ion solution. 25 When the normal cells were stimulated by the high concentration of potassium ions, the fluorescence intensity in the cells gradually decreased with the addition of the solution, as shown in Fig. 4.…”
mentioning
confidence: 91%
“…Fluorescence imaging is an effective method for monitoring molecular events in vivo in real time due to its non-destructive nature and capacity for high spatiotemporal resolution . Accordingly, several specific fluorescent probes have been developed for in vivo fluorescence imaging of NE. However, obtaining fine spatial resolution at depths beyond the optical diffusion limit remains a challenge for purely optical imaging methods . Therefore, developing probes that can improve the resolution, sensitivity, accuracy, and tissue penetration depth of bioimaging is an important issue in the field of bioimaging.…”
Section: Introductionmentioning
confidence: 99%